The struggle for celibacy : the culture of Catholic seminary life - Stanosz, Paul. (New York : Herder & Herder Book, 2006)
"Whether people defend or attack it, celibacy remains one of the most controversial and least understood aspects of Catholic priestly life. In this careful study, Fr. Paul Stanosz gives us a fresh approach to the issue. By interviewing seminarians and their instructors, he shows the variety of reasons that young men are drawn to priesthood and celibacy. He also makes us aware of the tremendous challenges such men face once they leave the supportive environment of their seminary community to begin their lives as diocesan priests."--BOOK JACKET.
1. Priests, seminaries, and celibacy -- 2. Celibacy and contemporary Catholicism -- 3. Reproducing celibacy as a cultural process -- 4. Observing celibacy : methodology for a study -- 5. Conceiving celibacy -- 6. Commitment production at St. Mark's Seminary -- 7. Reproducing father -- 8. Remaking seminaries -- App. A. Interview questionnaire guide for seminarians -- App. B. Interview questionnaire guide for administrators, faculty, and the archbishop -- App. C. Various reasons pro and con for mandatory celibacy.
Includes bibliographical references (p. 253-260) and index.
Keywords: Catholic Church -- Clergy -- Sexual behavior; Catholic Church -- Education; Celibacy -- Catholic Church; Clergy -- Training of; Theology -- Study and teaching -- Catholic Church